2000
DOI: 10.1177/14034948000280030401
|View full text |Cite
|
Sign up to set email alerts
|

Neck or shoulder pain and low back pain in Finnish adolescents

Abstract: The aim of this study was to investigate the prevalence and determinants of self-reported neck or shoulder pain (NSP) and low back pain (LBP) among 12-18-year-olds. A questionnaire was mailed to a nationally representative sample of 11,276 12-, 14-, 16- and 18-year-olds in 1991. The response rate was 77%. NSP was perceived at least once a week by 15% of 12-18-year-olds and LBP by 8%. Both symptoms were more prevalent among girls than among boys, and the prevalence increased with age. Among the determinants inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
97
4
12

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(130 citation statements)
references
References 36 publications
17
97
4
12
Order By: Relevance
“…The parts of the wellbeing index showed different associations with LBP, with the strongest correlation computed for the fitness item. The results may thus be in accordance with studies showing associations between LBP, much sitting [4] and infrequent ("seldom") physical activity [27]; a Ushaped association between level of physical activity and LBP has also been indicated [33]. An association between physical activity and wellbeing in adolescents seems to be well established [25].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The parts of the wellbeing index showed different associations with LBP, with the strongest correlation computed for the fitness item. The results may thus be in accordance with studies showing associations between LBP, much sitting [4] and infrequent ("seldom") physical activity [27]; a Ushaped association between level of physical activity and LBP has also been indicated [33]. An association between physical activity and wellbeing in adolescents seems to be well established [25].…”
Section: Discussionsupporting
confidence: 80%
“…The lifetime prevalence of LBP was somewhat higher than figures given in a recent review [4], but the prevalence of frequent LBP was in agreement with reports of 17% and 25% among 14-year-old boys and girls, respectively, in a Finnish survey [33]. The frequency of weekly headache was fairly similar to survey findings of 10% and 28% among 8-to 17-year-old Swedish boys and girls, [6], and 17% and 31% among 15-year-old Norwegian boys and girls, respectively [14].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Neuere epidemiologische Untersuchungen zur Prävalenz von Rückenschmerzen bei Schulkindern liegen für den europäi-schen und insbesondere skandinavischen Raum vor [27,28,29,30,31]. Bei finnischen Kindern wurden Prävalenz-raten für Rückenschmerzen von 8% [27] und 18% [28] berichtet. Die Lebenszeitprävalenz von Rückenschmerzen beträgt bei 12-bis 17-jährigen Schweizer Kindern und Jugendlichen 74%, in 69% der Fälle mit lumbaler Schmerzlokalisation [30].…”
Section: Rückenschmerzenunclassified
“…For example (Vikat et al, 2000), neck/shoulder pain is related to exercise among adolescents. El-Metwally et al (2007) identified vigorous exercise as a risk factor for traumatic musculoskeletal pain in preteens and early adolescents.…”
Section: Introductionmentioning
confidence: 99%